1993
DOI: 10.2323/jgam.39.429
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of bacteriophages lytic for Pediococcus halophilus, a halophilic lactic-acid bacterium, in soy sauce fermentation.

Abstract: Bacteriophages specific for Pediococcus halophilus, a group of halophilic lactic cocci used as starters for soy sauce fermentation, were isolated from fermenting soy sauce moromi-mash. Typical two of these phages, q57116 and qD-86, which propagate on P. halophilus NISL 7116 and D-86 respectively, were purified and studied for their morphology and some infecting properties. Morphotype of q57116 was Ackermann's Al having an isometric head of 87-96 nmi diameter and a contractile tail of 200 nm length. q5D-86 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…While the overall genome organisation satisfies all requirements for the completion of a virulent life cycle, the order of the modules in the genome differs slightly to the consensus genome arrangement of the Siphoviridae family. The morphological features of phage clP1 were very similar to those observed for Pediococcus phages previously reported in the literature (Caldwell et al, 1999;Uchida and Kanabe, 1993;Yoon et al, 2007). Nucleotide sequence analysis of the genome of phage clP1 indicated that this phage was not closely related to any previously characterized phages, highlighting the large level of diversity associated with this novel phage.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…While the overall genome organisation satisfies all requirements for the completion of a virulent life cycle, the order of the modules in the genome differs slightly to the consensus genome arrangement of the Siphoviridae family. The morphological features of phage clP1 were very similar to those observed for Pediococcus phages previously reported in the literature (Caldwell et al, 1999;Uchida and Kanabe, 1993;Yoon et al, 2007). Nucleotide sequence analysis of the genome of phage clP1 indicated that this phage was not closely related to any previously characterized phages, highlighting the large level of diversity associated with this novel phage.…”
Section: Resultssupporting
confidence: 68%
“…In spite of this there has been very little research on phages of pediococci apart from a small number of studies. These include a phage against P. halophilus from soy-sauce fermentation (Uchida and Kanabe, 1993), three temperate phages which were induced from P. acidilactici (Caldwell et al, 1999), and two prophage gene clusters which were reported in P. pentosaceus (Makarova et al, 2006). More recently, the isolation and characterisation of a lytic Pediococcus phage from fermenting cucumber brine was reported by Yoon et al (2007).…”
Section: Introductionmentioning
confidence: 96%
“…Phage was stable at all salinities between 1.8 and 150 However, phage was speficically unstable between 2 and 10 while being stable in both the lower(0.5to2 and the higher (10 to 150 salt range.This effect is probably due to the salting-in effect of ions which cause destruction of phage protein and DNA-protein complexes (Uchida and Kanbe, 1993).…”
Section: Bacteriophages Of Halophilic Bacteriamentioning
confidence: 99%
“…Lytic bacteriophages for two T. halophilus strains have recently been described (Uchida and Kanbe 1993). Although T. halophilus plasmids are cryptic , many studies have shown that various major traits, such as ranose, melibiose and sucrose utilization (Gonzalez and Kunka 1986;Hoover et al 1988) and bacteriocin production (Klaenhammer 1993) are plasmid-linked in P. acidilactici and P. pentosaceus.…”
Section: Introductionmentioning
confidence: 99%